Job satisfaction and its relation to the effectiveness of performance: Applied research on a sample of employees in the Federal board of supreme Audit (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aimed to study the job satisfaction of the staff of the Federal board of supreme Audit and its relation to the effectiveness of their performance, The questionnaire was adopted as a main tool in the collection of data and information from a random sample of (54) employees of the Federal board of supreme Audit. In light of this, the data were collected and analyzed and the hypotheses were tested using the statistical program (SPSS).The researchers reached a number of conclusions, the most important of which were: (1) the respondents' response to the variables of job satisfaction and the effectiveness of the performance were medium; (2) there was a significant relationship between job satisfaction and performance effectiveness of the staff of the Federal board of supreme Audit.